Abscisic, gibberellic, and salicylic acids effects on germination indices of corn under salinity and drought stresses. Issue 1 (2nd January 2022) - Bahrabadi, E.; Tavakkol Afshari, R.; Mahallati, M.Nassiri; Seyyedi, S. M.
ABSTRACT: The expression of genes that control germination-related processes in corn ( Zea mays L.) is influenced by environmental factors. Germination of seeds may be facilitated by hormonal priming. The purpose of this investigation was to quantify the effects of different germination temperatures [(5, 10, 15, 20, 25, 30, 35, and 40°C), NaCl-induced stress (0, −0.4, −0.8, and −1.2 MPa), and priming solutions (control, hydropriming, abscisic acid (ABA), gibberellic acid (GA), and salicylic acid (SA)] (Experiment 1). Effects of germination temperatures, PEG 6000-induced stress (0, −0.4, −0.8, and −1.2 MPa), and priming solutions were also evaluated separately (Experiment 2). In both cases, a completely randomized design with four replications was used. Increasing temperatures from 5 to 25°C gradually improved germination percentage and rate, whereas temperatures > 25°C decreased these indices. After imposing drought (PEG 6000-induced stress) or salinity (NaCl-induced stress) treatments, hormonal priming caused germination to occur at a lower base temperature, compared with the non-priming treatment. However, the effect of hormonal priming was dependent on temperature. At sub-optimal temperatures (< 25°C), the highest germination percentage and rate were recorded after GA priming. At above-optimal temperatures (> 25°C), ABA priming resulted in the highest germination percentage and rate. Moreover, hydrothermal time constant decreased in hormone-treated seeds. Based on coefficient of determination ( R 2 ) and root mean square error ( RMSE ), a dent-like model predicted cardinal temperatures more accurately than a beta model did. Generally, GA-, SA-, and ABA-priming were recommended under sub-optimal, optimal, and above-optimal temperatures, respectively.